Integrated Network Pharmacology and GC-MS–Based Metabolomics to Investigate the Effect of Xiang-Su Volatile Oil Against Menopausal Depression - Li, Yao; Yang, Xinyi; Chen, Shanshan; Wu, Lei; Zhou, Jinyong; Jia, Keke; Ju, Wenzheng (Frontiers in Pharmacology, 2021)
Menopausal depression perplexes a great number of women in later life. Xiangfu-Zisu (Xiang-Su), a traditional Chinese herbal pair composed of rhizomes of Cyperus rotundus L. (Xiangfu) and leaves of Perilla frutescens (L.) Britt. (Zisu), is frequently reported with antidepressant-like effects. The volatile oil from Xiangfu and Zisu has shown good antidepressant action, but its mechanism is still unclear. This study aimed to investigate the pharmacological mechanism of Xiang-Su (XS) volatile oil against menopausal depression through gas chromatography-mass spectrometry (GC-MS)-based network pharmacology and metabolomics. Firstly, actual detected components of XS volatile oil were performed ADME screening to obtain active constituents, and then duplicates of active constituents-related targets and menopausal depression-related targets were collected. These duplicates were considered as targets for XS volatile oil against menopausal depression, followed by GO and KEGG enrichment analysis. It showed that a total of 64 compounds were identified in XS volatile oil, and 38 active compounds were screened out. 42 overlapping genes between 144 compound-related genes and 780 menopausal depression-related genes were obtained. Results showed that targets of SLC6A4 and SLC6A3, regulation of serotonergic and dopaminergic synapse were involved in the antidepressant mechanism of XS volatile oil. Next, antidepressant-like effect of XS volatile oil was validated in menopausal rats by ovariectomy (OVX) combined with chronic unpredictable mild stress (CUMS). Behavioral tests, biochemical analysis, and GC-MS based non-targeted plasma metabolomics were employed to validate the antidepressant effect of XS volatile oil. Experimental evidence demonstrated that XS volatile oil reversed behavioral parameters in sucrose preference test (SPT), open-field test (OFT), forced swim test (FST), and serum estradiol levels in OVX rats. Furthermore, results of metabolomics indicated that XS volatile oil mainly acts on regulating metabolic pathways of phenylalanine, tyrosine and tryptophan biosynthesis, tyrosine metabolism, and tryptophan metabolism, which were corresponding with the above predicted results. These data suggest that network pharmacology combined with metabolomics provides deep insight into the antidepressant effect of XS volatile oil, which includes regulating key targets like SLC6A4 and SLC6A3, and pathways of serotonergic and dopaminergic synapse.